ANTIBIOGRAM OF PHARYNGEAL ISOLATES OF CHILDREN WITH PHARYNGOTONSILLITIS IN A SPECIALIST HOSPITAL IN GUSAU, NORTH-WESTERN NIGERIA - Garba BI; Muhammad AS; Mohammed F; Onazi SO; Ahmad MM; Yusuf T (Ntec Specialist, 2017)
Introduction: Pharyngotonsillitis is one of the common childhood infections caused by bacteria in 30 to 40% of cases. Bacterial causes are important due to the non suppurative sequalae caused by Streptococcus pyogenes and also associated complications. These microorganisms undergo constant changes and antibiotic resistance have been reported. Objective: To document organisms isolated from throat swab microscopy and culture with their antibiotic susceptibility pattern in children diagnosed with pharyngotonsillitis. Methodology: This was a retrospective analysis of throat swabs microscopy, culture and sensitivity results of children aged 0-13 years with a diagnosis of pharyngotonsillitis over a four year period. Results: Of the 144 results reviewed; 120 samples yielded 122 isolates, giving a culture positive yield of 83.3%. Males were 81 (56.2%) with a M:F ratio of 1.3:1. Majority of the children were under fives (58.3%). Gram positive organisms were 118 (96.7%), with Streptococcus pyogenes being the commonest organism isolated (79.5%), followed by Staphylococcus aureus (13.9%). Gentamicin (85.0%), Ofloxacin (64.2%) and Augmentin (51.7%) had the highest susceptibility rate, while the least was seen with Cefixime, Tetracycline, Levofloxacin and Netillin. Streptococcus pyogenes and Staphylococcus aureus were susceptible to Gentamicin and Ofloxacin, while all the Streptococcus pneumoniae were susceptible to Gentamicin. Multi drug resistance was seen with Providencia spp and Serratia marcescens. Conclusion: Streptococcus pyogenes was the commonest organism and Gentamicin, Ofloxacin and Augmentin were the antibiotics with the highest susceptibility. Gram negative organisms display high rate of multidrug resistance. Gentamicin could be considered as an option or an adjunct in the treatment of pharyngotonsillitis